Which Ratio of Areas Improves Vision Quality in Simultaneous Focus Optics? - Rio, David; Legras, Richard (Optometry and vision science, 2015)
To evaluate the impact of the center optical zone diameter (COZD) of center-near bifocal optics on the through-focus subjective quality of vision. Subjective image quality was assessed by 14 young, normally sighted subjects. Computed images of three high-contrast 20/50 letters were generated, across a range of object vergences from +2 diopters (D) to -4 D in 0.25-D steps. The center near optical zone addition power was +2.50 D, and the diameter of this center zone was varied in 10% steps to cover from 0% (single vision distance) to 90% of the 4.5-mm pupil diameter. Subjects rated image clarity of these computed images on a 0 to 5 scale, through a 3-mm pupil to limit the effect of their own aberrations. To quantify the efficiency of bifocal optics, we calculated the area under the through-focus subjective quality of vision curve. A criterion higher than 2 was judged to be an acceptable level of quality of vision, normalized by the naked eye condition. The average benefit of the optical profiles is highly subject dependent (i.e., from 0.8 to 1.9), potentially explaining why some subjects are not satisfied with simultaneous vision multifocal corrections. Averaged across subjects, the best benefit (i.e., 1.42) was obtained with a COZD covering 40% of the pupil area, whereas the 20, 30, and 50% profiles provide slightly lower benefit (i.e., ∼1.35). A COZD covering 20% of the pupil area equalized distance and near quality of vision. Quality of vision with bifocal optics is highly subject dependent. Peripheral rays do not seem to play an important role in the through-focus quality of vision, as the central pupil area is more heavily weighted in determining subjective image quality.